Late-onset ulnar neuritis following treatment of lepromatous leprosy infection. - Trevor Wellington; Christina Schofield (Public Library of Science (PLoS), 2019)
Neuritis is a frequent complication of Myocobacteria leprae infection and treatment due to the variety of mechanisms through which it can occur. Not only can mycobacterial invasion into peripheral nerves directly cause damage and inflammation, but immune-mediated inflammatory episodes (termed leprosy reactions) can also manifest as neuritis at any point during infection. Treatment of leprosy reactions with thalidomide can also lead to neuritis due to an adverse drug effect. Neuritis can emerge years after initial diagnosis and treatment, although it is most frequently found at time of diagnosis or early into the treatment course. Treatment of neuritis is dependent on high-dose corticosteroid therapy as well as therapy for suspected underlying etiology. Here, we present a case of ulnar neuritis presenting in a patient with lepromatous leprosy four years after treatment of initial infection, with subsequent improvement after corticosteroid burst while maintained on thalidomide therapy.